Integration of Citizenship Values in Public Relations Strategy in the Digital Era - M. Dwi Cahyono; Sutiah Sutiah; Moh. Padil (Universitas Negeri Malang, 2025)
The purpose of this study is to describe civic values that can be integrated into public relations strategies, efforts to integrate civic values into public relations practices, and obstacles encountered in the process of integrating civic values. This study uses a qualitative method with a case study approach. This study was conducted in several madrasas that actively utilize digital media, with research subjects including public relations managers, teachers, and related parties. Data were collected through in-depth interviews, observation, and documentation, then analyzed using content analysis techniques through the stages of data reduction, data presentation, and conclusions. The results of the study indicate that civic values integrated into public relations strategies include nationalism, tolerance, responsibility, active participation, and digital ethics. Integration efforts are carried out through the use of digital media as a means of educational communication, digital ethics campaigns, and collaboration with various parties. The integration process still faces obstacles such as limited human digital resource competency, a focus on public relations that tends to be promotional, and suboptimal strategic planning based on civic values.